Chronic Psychological Stress Was Not Ameliorated by Omega-3 Eicosapentaenoic Acid (EPA) - Bradbury, Joanne; Myers, Stephen P.; Meyer, Barbara; Brooks, Lyndon; Peake, Jonathan; Sinclair, Andrew J.; Stough, Con (Frontiers in Pharmacology, 2017)
Background Chronic psychological stress and mental health disorders are endemic in Western culture where population dietary insufficiencies of omega-3 fatty acids (n-3FA) from seafood have been observed. Objective This study was designed to test for a causal relationship between one of the most active components of fish oil, eicosapentaenoic acid (EPA), and chronic psychological stress. Method A randomized double-blind, placebo-controlled clinical trial with parallel-assignment to two groups was designed (Trial Id: ACTRN12610000404022). The interventions were four EPA-rich fish oil capsules per day, delivering 2.2 g/d EPA (and 0.44 g/d DHA), or identical placebo (low-phenolic olive oil capsules with 5% fish oil to aid blinding). The primary outcome was the between-group difference on the Perceived Stress Scale (PSS-10) after 12 weeks supplementation. An a priori power analysis determined that group sizes of 43 would provide 80% power to detect a significant between-group difference of 12.5%, at α = 0.05. Ninety community members (64 females, 26 males) reporting chronic work stress were recruited via public advertising in northern NSW, Australia. Results At baseline the omega-3 index (EPA + DHA as % to total fatty acids in red blood cell membranes) was 5.2% in both groups (SD = 1.6% control group; 1.8% active group). After supplementation this remained stable at 5.3% (SD = 1.6%) for the control group but increased to 8.9% (SD = 1.5%) for the active group, demonstrating successful incorporation of EPA into cells. Intention-to-treat (ITT) analysis found no significant between-group differences in PSS outcome scores post-intervention (b = 1.21, p = 0.30) after adjusting for sex (b = 2.36, p = 0.079), baseline PSS (b = 0.42, p = 0.001) and baseline logEPA (b = 1.41, p = 0.185) (F(3,86) = 8.47, p < 0.01, n= 89, R-square = 0.243). Discussion Treatment increased cell membrane EPA but, contrary to the hypothesis, there was no effect on perceived stress. Limitations included an imbalance of gender in groups after randomization. Larger trials with groups stratified for gender may be required to confirm these findings. Conclusion This study demonstrated that 2.2 g/day of EPA for 12 weeks did not reduce chronic psychological stress.